Applying an intraoperative predictive indicator for postoperative pancreatic fistula: randomized preclinical trial - Pausch, Thomas; Mitzscherling, Clara; Aubert, Ophelia; Liu, Xinchun; Gesslein, Bodil; Bruckner, Thomas; Kommoss, Felix; Golriz, Mohammad; Mehrabi, Arianeb; Hackert, Thilo (The British journal of surgery, 2021)
Leaking pancreatic fluid can contribute to postoperative pancreatic fistula (POPF), which can complicate pancreatic surgery. Surgeons lack reliable tools to ide
Gesehen am 25.06.2021